SEJARAH PEMBENTUKAN KECAMATAN KANDIS KABUPATEN SIAK (2001-2002) - Siti Nur; Bedriati Ibrahim; Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The formation of an area is always needed to achieve good governance and service for the welfare of the community in accordance with the capabilities of each region in the process of development and regional growth. Every region in this world certainly has its own history both in terms of the process of formation, naming and also the development of the area which is certainly different from other regions, making it unique. Similarly, the Kandis Subdistrict, Siak Regency, is a district that has a long history in its formation process. The purpose of this study was to find out the history of formation, to find out the desire of the community to form Kandis into a Subdistrict, to find out the efforts and processes of the people's struggle so that the Kandis District of Siak Regency was formed (2001-2002), and to determine the what factors are supporting and inhibiting the formation of Kandis District, Siak Regency. The method used is historical (historical), where data is collected through observation, documentation, interviews, and literature. Data analysis was carried out in a qualitative manner. The time of research began since the publication of the pre-research letter until the completion of the final revision of the author's thesis. The results showed that the original Kandis tribe was a sakai tribe, with the Pekanbaru-Dumai road even going to North Sumatra through Kandis which included the East Sumatra crossing road by Chevron which made Kandis grow rapidly with an increase in the population in each year, with developments and the population is increasing and while the range of control and public services that are less than optimal raises people's aspirations to make Kandis a district. With a long process of community struggle finally on December 31, 2002 Kandis officially became Kandis District.Key Words: History, Formation, Kandis Distric